Effect of Moisture to Indirect Tensile Strength of Asphalt Concrete - Abdul Wahid, Siti Nur Amera; Shamshuddin, Mustafa Kamal (Recent Trends in Civil Engineering and Built Environment, 2021)
Asphalt concrete is the most widely used in flexible pavement construction and other purposes in this worldwide. Including Malaysia, other countries also prefer to construct the road by using asphalt concrete and still learning about its mechanical and physical properties. In this study, problem of the asphalt concrete properties such as moisture effect to the asphalt concrete was discussed. It was to obtain the knowledge of moisture that presence in asphalt concrete. Basically, the effect of moisture to the asphalt concrete is resulting to the distress regarding to the adhesion and cohesion mechanisms in asphalt concrete itself. Losing of adhesion contributed by the presence of moisture getting into bitumen and aggregates resulting stripping damage to the asphalt pavement. The other mechanism which is losing of cohesion within the bitumen itself that resulting in a reduction in asphalt mix stiffness. The percentage of air void in compacted asphalt concrete sample and its effect to the asphalt concrete behaviour was distinctly discussed. The effect of moisture in asphalt concrete to Indirect Tensile Strength was also determined and discussed in this study. ITS test was conducted in this study to determine the Indirect Tensile Strength value and Tensile Strength Ratio to access the moisture susceptibility of asphalt concrete.